Hemodynamic and ventilatory parameters in rabbits anesthetized with isoflurane submitted to pressure controlled ventilation with or without PEEP - Aidar, E. S.A. [UNESP] (2020)
Pressure controlled ventilation with or without positive end-expiratory pressure (PEEP) was compared in rabbits, which were divided into three groups denominated GP (pressure cycled ventilation group), GPP (pressure cycled ventilation with PEEP group) and GE (spontaneous ventilation group-control group). The animals were anesthetized with isoflurane in a gas rebreathing circuit for two hours. The means of mean arterial pressure (MAP) and systolic blood pressure (SBP) remained slightly below normal values in all groups. There was a significant decrease in MAP and SBP in the group submitted to PEEP (GPP) over time. The partial pressure of arterial carbon dioxide (PaCO2) was higher in GPP when compared to the other groups, inducing respiratory acidosis after one hour. The end-expired carbon dioxide concentration (ETCO2) presented slightly elevated means in the GP, while the GPP presented higher means, possibly related to the decrease in tidal volume in this group. Based on these results it was concluded that the use of PEEP led to acidemia that worsened over anesthetic time. In addition, prolonged isoflurane anesthesia promotes cardiorespiratory depression, regardless the ventilatory mode employed.